FAKTOR PENYEBAB PESERTA DIDIK MELAKUKAN BULLYING DI SMP NEGERI 15 PADANG - Nazly, Putri Purnama (Bimbingan dan Konseling, 2014)
Violence conducted by students is much more in news than before , one of the violence is about bullying.Bullying is a behavior of aggressive which is very dangerous behavior , itâs like violence, brawl and bullying, whereIs the counseling teacher be charged to give more attention to handle the situation to the students who involvedbullying. The purpose that we want in this research is the factor cause why the students do bullying in SMPN 15 inpadang, focus of the research is about school environment is not good. Seniority never be solved, the teacher givethe example to the student how bad the bullying, disharmony in home, and character of children. The research dowith qualitative approach which is descriptive is to describe the cause, fact and reality in the area is about factorscausing the students to do a bullying. While the informant in the research is : the students, the victim of the students,counseling teachers, and classroom teacher. The instrument that the researchers use in the research is interview andstudy documentation technique use in data processing by data reduction, the presentation of data and conclusion.Result of the research reveal that the factors can make the students do the bullying is violence in schoolenvironment, and the teachers give an appropriate example and donât respect the students ,the seniority unresolvedand seniors who behave what they want. Aggressive ,spiteful student and less of the communication students withtheir parents. Based on the research recommended to the students, counseling teachers and related people toovercome the bullying, itâs like brawl, fight, violence, bullying and humiliation at school.